Intermediate technology - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1992)
Intermediate Technology Development Group (IT) is a non-governmental international development agency which works with rural and pert-urban communities in Developing Countries. Intermediate Technology was founded in the 1960s by Dr E F Schumacher,...